2007
DOI: 10.1002/jcp.21059
|View full text |Cite
|
Sign up to set email alerts
|

AND‐34/BCAR3 differs from other NSP homologs in induction of anti‐estrogen resistance, cyclin D1 promoter activation and altered breast cancer cell morphology

Abstract: Over-expression of AND-34/BCAR3/NSP2 (BCAR3) or its binding-partner p130Cas/BCAR1 generates anti-estrogen resistance in human breast cancer lines. Here, we have compared BCAR3 to two related homologs, NSP1 and NSP3/CHAT/SHEP, with regards to expression, anti-estrogen resistance, and signaling. BCAR3 is expressed at higher levels in ERα-negative, mesenchymal, than in ERα-positive, epithelial, breast cancer cell lines. Characterization of "intermediate" epithelial-like cell lines with variable ER-α expression re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
77
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(83 citation statements)
references
References 32 publications
6
77
0
Order By: Relevance
“…This is in line with earlier suggestions that the level of the BCAR1-BCAR3 complex in breast cancer cell lines correlates with malignancy more closely than the levels of each individual protein (23). Therefore, disrupting the complex could sensitize breast cancer cells to chemotherapeutic drugs and favor reversion to a less malignant state.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…This is in line with earlier suggestions that the level of the BCAR1-BCAR3 complex in breast cancer cell lines correlates with malignancy more closely than the levels of each individual protein (23). Therefore, disrupting the complex could sensitize breast cancer cells to chemotherapeutic drugs and favor reversion to a less malignant state.…”
supporting
confidence: 92%
“…The Physical Association of BCAR1 and BCAR3 Leads to the Stabilization of Both Proteins-The increase in phosphorylated BCAR1 is accompanied by protein stabilization resulting in higher overall BCAR1 levels, which has been reported to be induced by BCAR3 and the related NSP3 (23,40). Accordingly, we found that both BCAR3 wild-type and the R748E mutant similarly increase BCAR1 protein levels, whereas the L744E/ R748E double mutant has lost this ability (Fig.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations